Application of the “Principle of the First Reviser” to Determine the Correct Spelling for a Recently Described Stingray Species from the Western South Atlantic Ocean (Chondrichthyes, Myliobatiformes, Dasyatidae) - Santos, Hugo Ricardo Secioso; Carvalho, Marcelo Rodrigues de (Arquivos do Museu Nacional, 2021)
Two distinct spellings are present in a recent description of a new species of whiptailed stingray from the Western South Atlantic Ocean: Dasyatis hipostigma and Dasyatis hypostigma. In response to inquiries from researchers concerning the correct spelling of this nominal species, the original authors hereby invoke the Principle of the First Reviser, as determined by the International Code of Zoological Nomenclature (Article 24.2), to establish its correct spelling as Dasyatis hypostigma. Num recente trabalho de descrição de uma nova espécie de raia-manteiga do oceano Atlântico Sul Ocidental são observadas duas grafias distintas: Dasyatis hipostigma e Dasyatis hypostigma. Em resposta a consultas de pesquisadores sobre qual seria a grafia correta para esta espécie nominal, os autores originais fazem uso do Princípio do Primeiro Revisor, conforme previsto no Código Internacional de Nomenclatura Zoológica (Artigo 24.2), para estabelecer a sua grafia correta como Dasyatis hypostigma.